2017
DOI: 10.1002/term.2261
|View full text |Cite
|
Sign up to set email alerts
|

The roles and perspectives of microRNAs as biomarkers for intervertebral disc degeneration

Abstract: MicroRNAs (miRNAs) are highly conserved molecules that regulate protein levels post-transcriptionally. Aberrant miRNA expression presents in various musculoskeletal disorders, such as osteoporosis, osteoarthritis and rheumatoid arthritis. The expression levels of miRNAs are characterized by endogenous properties and tissue specificity. This raises the possibility that miRNAs could serve as useful clinical biomarkers in the diagnosis of certain diseases. Intervertebral disc degeneration (IDD) is one of the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 87 publications
(100 reference statements)
0
52
0
Order By: Relevance
“…In addition, no studies were found that studied molecular biomarkers in relation to progression of DD. This is surprising, as biomarkers are subject of many studies in relation to DD, but are presumably related to the onset of DD and not progression, which is beyond the scope of this review. Second, there was a high heterogeneity between studies regarding the definition of DD and its progression, which made it impossible to pool data.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, no studies were found that studied molecular biomarkers in relation to progression of DD. This is surprising, as biomarkers are subject of many studies in relation to DD, but are presumably related to the onset of DD and not progression, which is beyond the scope of this review. Second, there was a high heterogeneity between studies regarding the definition of DD and its progression, which made it impossible to pool data.…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, GPC6 expressed in chondrocytes of mouse growth plates, and might induce the degeneration of cartilage endplates and even structural abnormal ossification by WNT and hedgehog signaling pathways. (Campos‐Xavier et al, ; Daly et al, ; Zhou et al, ). Secondly, GPC6 may affect the main components of the nucleus pulposus (NP) by BMP‐7, such as type I and type II collagen (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, GPC6 may be associated with LDH by causing osteoporosis (Dequeker, 1997;Im & Kim, 2014) as well as play an important role in cartilage damage by WNT pathway, whose structures are a main part of the endplate (van den Bosch et al, 2015;Daly, Ghosh, Jenkin, Oehme, & Goldschlager, 2016). In addition, GPC6 is also reported to be responsible for LDD by changing the internal environment of nucleus pulposus (NP) cells (Zhou et al, 2017). Thus, we highlighted the importance of GPC6 in the development of LDH, and speculated that single-nucleotide polymorphisms (SNPs) of GPC6 are involved in LDH occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…184 Notably, expression profiling studies have identified a number of dysregulated miRNAs in human degenerated IVDs when compared to control specimens. 185188 Another study reported higher levels of miR-100 in human lumbar degenerated discs compared to traumatized, non-degenerated human specimens and that altered expression levels correlated with FGFR1. 189 A polymorphism in pre-miR-125a (Rs12976445) has been shown to result in a significant reduction in the amount of mature miR-125a by compromising its processing, thereby leading to less efficient inhibition of target genes.…”
Section: Mirnas Associated With Skeletal Disease and Other Orthopaedimentioning
confidence: 99%